2015
DOI: 10.1002/wps.20251
|View full text |Cite
|
Sign up to set email alerts
|

Etiological overlap between obsessive‐compulsive disorder and anorexia nervosa: a longitudinal cohort, multigenerational family and twin study

Abstract: Obsessive-compulsive disorder (OCD) often co-occurs with anorexia nervosa (AN), a comorbid profile that complicates the clinical management of both conditions. This population-based study aimed to examine patterns of comorbidity, longitudinal risks, shared familial risks and shared genetic factors between OCD and AN at the population level. Participants were individuals with a diagnosis of OCD (N519,814) or AN (N58,462) in the Swedish National Patient Register between January 1992 and December 2009; their firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
1
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 124 publications
(88 citation statements)
references
References 27 publications
4
77
1
6
Order By: Relevance
“…First, the strong positive genetic correlations of anorexia nervosa with obsessive-compulsive disorder and neuroticism reinforce clinical and epidemiological observations. AN is commonly comorbid with OCD and twin studies have reported high twin-based genetic correlations (27). High neuroticism in adolescence predicts subsequent onset of AN (1).…”
Section: Discussionmentioning
confidence: 99%
“…First, the strong positive genetic correlations of anorexia nervosa with obsessive-compulsive disorder and neuroticism reinforce clinical and epidemiological observations. AN is commonly comorbid with OCD and twin studies have reported high twin-based genetic correlations (27). High neuroticism in adolescence predicts subsequent onset of AN (1).…”
Section: Discussionmentioning
confidence: 99%
“…Originally, the intention was to include males in the AN group, but at the time of recruitment there were no eligible male patients. However, including males in the study would have given additional information on whether eating behaviours frequently seen in ASD are even more common in male patients with AN [34, 35]. Furthermore it is a limitation that the instruments SWEAA and AQ were self-report measurements.…”
Section: Limitationsmentioning
confidence: 99%
“…Replicated heritability estimates for AN have ranged between 48%−74% depending on the definition of AN used [*5]. Twin studies have also suggested there is shared genetic risk between AN and multiple psychiatric phenotypes including other eating disorders [9], obsessive compulsive disorder [10], major depression, and suicide attempts [11]. Although family and twin studies provided initial evidence of the role of genetic factors in AN, these methods cannot identify which genetic variants are involved in risk.…”
Section: Historical Genetic Findingsmentioning
confidence: 99%